ENTERTAINMENT AND VIDEO GAMES - Bryn, Abby (Hollywood, FL.: MASON CREST, 2022)
"Video games and entertainment media are meant to be fun, but games and television shows have also been no stranger to controversy. Politicians, teachers, and parents groups have accused them of glorifying violence, leading to a sedentary lifestyle, and other issues. Others note the potential benefits of entertainment media. The discussion is not clear-cut, and as such, the consensus can be difficult to grasp. This book aims to provide much-needed perspective"--Back cover.
Includes index.
Keywords: Video games -- Social aspects; Video games -- Psychological aspects; Mass media -- Social aspects; Mass media -- Psychological aspects